IPTEKS PENGENDALIAN AKTIVA TETAP PADA PT.PLN (PERSERO) UNIT INDUK PEMBANGUNAN SULAWESI BAGIAN UTARA - Savsavubun, Regina Valentine; Pinatik, Sherly (Universitas Sam Ratulangi, 2018)
Economic developments that increasingly affect the activities of each company in gaining profit (profit), both private companies and government companies. Every company in carrying out its business cannot be separated from the use of assets (assets) which are relatively fixed in nature. Fixed assets are permanent assets and are owned or used by companies with long periods of time and not for sale. The role of fixed assets is very important in producing goods and services. As with PT PLN (Persero) Unit Induk Pembangunan Sulawesi Bagian Utara, one of the largest companies in Indonesia if it does not use the fixed asset control procedures, it tends to occur fraud and misuse or waste from the use of fixed assets because the structure of the control of fixed assets is very necessary to maintain the security of property of PT PLN (Persero) the Parent Unit of North Sulawesi Development itself, check the truth in accounting data, and encourage policies that have been set by the leadership.Keywords: purpose of fixed assets control, PT. PLN (Persero) UIP SULBAGUT